Exploring the Viability of the Ranked Discrepancy Model by Comparing the Weighted Total Index Approach and the Borich Model: A Case of Learning Needs Assessment of Career Guidance Teachers - Hee-Jun Choi; Ji-Hye Park (Education Sciences, 2023)
The ranked discrepancy model (RDM) is a relatively novel needs assessment approach and is optimized for addressing ordinal and non-normally distributed data. This study aimed to explore the viability of the RDM by comparing the results obtained from it with those obtained using two other long-standing needs assessment models, and to prioritize the learning needs of secondary school career guidance teachers in South Korea using the RDM as an initial effort to improve the pre-service and in-service educational programs of teachers. Data were collected from 75 career guidance teachers by using a survey questionnaire. The results from the RDM, the weighted total index (WTI) approach, and the Borich model demonstrated a great deal of consistency in terms of the rankings of career guidance teachers’ learning needs. This implies that the RDM is a useful quantitative method for needs assessment in cases involving ordinal items, cross-sectional data, or non-normally distributed data. This study also revealed that “providing and utilizing occupational information” is the biggest shortfall among the job tasks required of secondary school career guidance teachers, compared to its importance. Uncertainty about the future might make it more difficult for career guidance teachers to provide students with the appropriate occupational guidance.